Reinstatement of Gutierrezia leucantha Cabrera (Asteraceae, Astereae). Issue 2 (2nd July 2016) - Ratto, F.; Bartoli, A.
Abstract : Gutierrezia leucantha Cabrera, a species previously included in the synonymy of Gutierrezia gillesii Griseb., is reinstated as a distinct species. A morphological description is presented with information on distribution and habitat. A key to distinguish this species from its congeners with white ray florets is provided.